Environmental and landscape studies on some ornamental plants used in north coast villages of Egypt - Sharaf El-Din, M. N.; Hussein, H. A. A.; Abdalla, M. Y. A.; Allam, B. A. F. (2007)
The current Investigation aimed to study the effects of environmental and landscape conditions on some ornamental plants used for landscape planning in some North Coast Villages of Egypt during the successive years from 2003 to 2006. Three resorts at the North Coast of Egypt; Costa Dell Sol. Green Beach and Marina (phase 5). Were chosen to carry out this study. In each resOrt. Certain vegetative measurements were conducted to determine the growth and development of some ornamental plants growing at the distances of 100 and 500 m from the seashore. These measurements were carried out at the four c1imatic seasons (autumn. winter, spring and summer).
Includes references.
Summary in Arabic.
1
Keywords: Human ecology -- Study and teaching; Landscapes; Sandy soils; Ornamental plants